2017
DOI: 10.1155/2017/3103272
|View full text |Cite
|
Sign up to set email alerts
|

A Cystine‐Rich Whey Supplement (Immunocal®) Provides Neuroprotection from Diverse Oxidative Stress‐Inducing Agents In Vitro by Preserving Cellular Glutathione

Abstract: Oxidative stress is a principal mechanism underlying the pathophysiology of neurodegeneration. Therefore, nutritional enhancement of endogenous antioxidant defenses may represent a viable treatment option. We investigated the neuroprotective properties of a unique whey protein supplement (Immunocal®) that provides an essential precursor (cystine) for synthesis of the endogenous antioxidant, glutathione (GSH). Primary cultures of rat cerebellar granule neurons (CGNs), NSC34 motor neuronal cells, or HT22 hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 66 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…Recently, the antioxidant potential of Immunocal ® , a whey protein supplement enriched in cystine-donor proteins has been studied. Cystine, the oxidized form of cysteine, is resistant to proteolysis and can be transported via the blood flow to target organs and tissues, where it is absorbed by cells and reduced to two cysteine molecules (Winter, Ross et al 2017). Rat cerebellar granule neurons treated with a medium containing 3.3 % Immunocal ® for 24 h were protected from the drop in GSH induced by a pro-apoptotic drug termed HA14-1 (Zimmermann, Loucks et al 2007;Winter, Ross et al 2017).…”
Section: Whey Proteinsmentioning
confidence: 99%
“…Recently, the antioxidant potential of Immunocal ® , a whey protein supplement enriched in cystine-donor proteins has been studied. Cystine, the oxidized form of cysteine, is resistant to proteolysis and can be transported via the blood flow to target organs and tissues, where it is absorbed by cells and reduced to two cysteine molecules (Winter, Ross et al 2017). Rat cerebellar granule neurons treated with a medium containing 3.3 % Immunocal ® for 24 h were protected from the drop in GSH induced by a pro-apoptotic drug termed HA14-1 (Zimmermann, Loucks et al 2007;Winter, Ross et al 2017).…”
Section: Whey Proteinsmentioning
confidence: 99%
“…By preserving brain GSH, Immunocal® could mitigate several of the secondary injury mechanisms that are activated by TBI. In this context, we recently demonstrated that Immunocal® is broadly neuroprotective in vitro and rescues primary cerebellar neurons and various neuronal cell lines from a number of stressors including oxidative damage, nitric oxide, and excitotoxicity (Winter et al, 2017). All of these stressors are believed to contribute to the secondary injury processes post-TBI.…”
Section: Discussionmentioning
confidence: 99%
“…All of these stressors are believed to contribute to the secondary injury processes post-TBI. Importantly, the neuroprotective effects of Immunocal® observed in cell culture are dependent on the de novo synthesis of GSH (Winter et al, 2017). Thus, it seems probable that at least the neuroprotective actions of Immunocal® observed in this mouse model of TBI are due largely to its capacity to act as a cysteine delivery system and thereby, a precursor pool for GSH synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…ROS can damage proteins by oxidation of amino acids, because all amino acids are susceptible to oxidation, especially cysteine and methionine [ 92 , 93 ]. Protein oxidation is initiated by interactions with hydroxyl radicals inducing protein modifications, such as protein-protein cross-linking, amino acid side chain modification, protein fragmentation by oxidation of the protein backbone, and enzyme inactivation resulting in activity loss.…”
Section: The Role Of Oxidative Stress In Parkinson’s Diseasementioning
confidence: 99%